RANCANG BANGUN ALAT BLANKET WARMER BERBASIS ARDUINO - Andrianto, Dian; Muslihun; Wawan Setiawan, Lalu (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2022)
Advances in technology have made health services more developed, especially in anesthesia. Anesthesia is an attempt to relieve pain. The post-anesthesia recovery period is needed as a time with a high risk for complications. It was found that 2.5% of patients experienced complications after undergoing anesthesia. One of the complications that will arise after anesthesia is hypothermia. The negative effects of hypothermia on patients include increased bleeding risk, myocardial ischemia, longer post-anesthesia recovery, impaired wound healing, and the risk of infection. Blanket warmer is a device that is used for the patient's body when experiencing hypothermia. This tool basically utilizes the heat energy generated by the heater and uses a blower as a heat conducting medium, and a DS18B20 sensor to unite the patient's body temperature and the thermistor temperature sensor as a detector of hot air produced by the heater and blower. The results of measuring the comparison of patient temperature between the research tool and a digital thermometer get the largest percentage of 0.1% where the largest error percentage is in samples 1 and 2. 3.